Cover Crop Management in a Sauvignon Blanc/Ramsey Vineyard in the Semi-Arid Olifants River Valley, South Africa. 2. Effect of Different Cover Crops and Cover Crop Management Practices on Grapevine Performance - Fourie, J.C.; Louw, P.J.E.; Agenbag, G.A. (South African Journal of Enology and Viticulture, 2016)
The trial was conducted over a period of ten years (1993/94 to 2002/03) on a sandy soil in a Sauvignon blanc/ Ramsey vineyard near Lutzville (31o35’S, 18o52’E), situated in the semi-arid Olifants River Valley of the Western Cape. Fourteen treatments, consisting of three grain species and four legumes, managed according to two cover crop management practices, were included. One management practice consisted of cover crops which were sown annually and full surface, post-emergence chemical control which was applied before bud break and when the berries reached pea size (BB). The second management practice consisted of cover crops which were sown biennially. Post-emergence chemical control was applied to the vine row before bud break and full surface when the berries reached pea size (AB). From 1999/2000 to 2002/03 the cover crops were sown annually, while the full surface post-emergence control applied at the end of November was advanced to mid-October. Two treatments in which Avena sativa L. v. Saia (‘Saia’ oats) and Vicia dasycarpa Ten. (grazing vetch) were sown annually, controlled mechanically in the work row and chemically in the vine row from bud break to harvest (MC), were also applied. These treatments were compared to a control, in which no cover crop was sown and MC was applied. A treatment in which no cover crop was sown and BB was applied (weedchem), was also included. During the third growing season of the vines (1994/95), the grapevine shoot mass of the BB treatments of grazing vetch and Medicago truncatula Gaertn. v. Paraggio (‘Paraggio’ medic) was significantly more than that of the AB and MC treatments, with the exception of Secale cereale L. v. Henog (AB) and grazing vetch (MC). The first harvest (1994/95) from the grapevines in the BB treatments was significantly higher than that of weedchem and the MC treatments. The grape yield of the BB treatments, grazing vetch (AB) and Ornithopus sativus L. v. Emena (pink Seradella) (AB) was significantly more than that of weedchem and the control during the 1997/98 season. The NO3-N concentration in the leaf petioles in all the cover crop treatments was, with the exception of the AB treatments of rye, M. truncatula Gaertn. v. Parabinga (‘Parabinga’ medic) and grazing vetch, significantly higher than that in weedchem and the control, as measured during the 1994/95 season. The NO3-N concentration in the leaf petioles of the BB and AB treatment of a species differed significantly. The N concentration in the juice of the cover crop treatments during the 1995/96 season was, with the exception of ‘Saia’ oats (MC) and ‘Parabinga’ medic (AB), significantly higher than that of weedchem and the control. During the 1998/99 season, the N concentration of the juice in the BB and AB treatments of grazing vetch and pink Seradella was significantly higher than that of the MC treatments, two rye treatments, weedchem and the AB treatments of the other cover crops. The concentration of Ca in the juice of the cover crop treatments was, with the exception of the pink Seradella treatments, significantly higher than that of weedchem and the control. Wine quality did not differ between treatments.